HLA class-1 molecules in Iraqi patients with rheumatoid arthritis . A sporadic & familial study - Al-Haidary, batool A.; Mousawy, Khalida M.; Al-khafaji, Jasim; Al-ezzy, Mustafa (Journal of the Faculty of Medicine Baghdad, 2006)
Baghdad: